FACTORS THAT AFFECT ACHIEVEMENT MOTIVATION ON STUDY ACHIEVEMENT STUDENT IN ACCOUNTING MAJOR FACULTY OF ECONOMY AND BUSINESS BRAWIJAYA UNIVERSITY - Albertus Arjuna Kuncoro Putra; Endang Mardiati (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was aimed to find out the effect of parental involvement (X1), expectation and parental support (X2), campus environtment (X3), and lecturer expectation and support (X4) effect on achievement motivation (Y1) also to find out the effect of achievement motivation (Y1) on learning achievement (Y2) of students class of 2010 from faculty of economics in Brawijaya University Malang. The respondents who took part in this reasearch were 130. this research used survey and data method of students' GPA.  The researcher was using the classical assumption test, regression test, as well as testing the effect hypothesis  of independent variables.  The result  (R2) of those  four  independent variable  on achievement motivation is 83,9%, while the rest 35,8% affected by other variables which were not examined in this research. Keywords: parental involvement, expectations and  parental support, campus environtment, expectation and lecturer support, achievement motivation, student achievement.